Meningkatkan Pemahaman Konseptual Mendalam Siswa dalam Fisika Melalui Demonstrasi Video: Tinjauan Literatur Sistematis - Thorieq Moh. Yusuf; Uswatun Hasanah; Ammase S (Universitas Garut, 2025)
This systematic literature review investigates the effectiveness of video demonstrations in enhancing students' deep conceptual understanding in physics education. Adopting the PRISMA 2020 guidelines, a comprehensive search was conducted on the Scopus database for articles published between 2015 and 2025. A final selection of 20 high-impact empirical studies involving high school and university students was analyzed using thematic synthesis. The results reveal that video interventions successfully foster deep understanding only when designed to trigger active cognitive processing. Key effective strategies include leveraging cognitive conflict to correct misconceptions, utilizing video analysis tools (e.g., Tracker) for mathematical modeling, and employing simulations for abstract quantum concepts. Conversely, passive video consumption proves insufficient for conceptual change. The study concludes that video demonstrations function as effective cognitive scaffolds when coupled with interactivity, such as embedded questions and inquiry-based tasks. These findings imply that physics educators should transition from using videos as static illustrations to utilizing them as tools for active scientific analysis.